KINO KÓRKEM ÓNERINIŃ ZAMANAGÓY MEDIADAǴÍ ORNÍ (ART AND CULTURE BULLETIN, 2025)
The article examines and analyzes the role of cinema in modern media. The main roles of media art were considered.
Keywords: modern media; public consciousness; culture; values; media literacy; film language; image.